An Analysis Of Translation Methods Used By Students In Translating Analytical Exposition Text From English Into Indonesian At Grade Xi Of Sma Swasta Budi Utomo Medan - Situmorang, Marnala Yekhonya Winda Jelita; Napitupulu, Fenty Debora; Sipayung, Kammer Tuahman (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
The purpose of this study was to identify the translation methods used by Grade XI students of SMA Swasta Budi Utomo Medan and to determine the dominant method in translating an analytical exposition text from English into Indonesian. This study applied Larson’s (1984) translation theory, focusing on Form-Based, Communicative, and Idiomatic Translation. A descriptive qualitative design was employed. The data were obtained from the translations of 21 students based on a text entitled The Importance of Learning English, which was divided into 30 segments, resulting in 630 translation units. The data were analyzed using the interactive model of Miles and Huberman (2014). The findings revealed that Form-Based Translation was the most dominant method (352 occurrences; 55.9%), followed by Communicative Translation (240 occurrences; 38.1%) and Idiomatic Translation (38 occurrences; 6.0%). Furthermore, 13 students (61.9%) were categorized as predominantly form-based translators, while 8 students (38.1%) were communicative translators, and none were idiomatic. These findings indicate that students tend to prioritize source language structure rather than natural meaning in the target language, suggesting the need to enhance their communicative translation competence.